2-Pyridone-functionalized Aza-BODIPY photosensitizer for imaging-guided sustainable phototherapy. (November 2018) - Xiao, Wanyue; Wang, Peng; Ou, Changjin; Huang, Xiaoyu; Tang, Yunyun; Wu, Meiyan; Si, Weili; Shao, Jinjun; Huang, Wei; Dong, Xiaochen
Abstract: To overcome irradiation-dependence of cancer phototherapy, a near infrared aza-BODIPY-based photothermogenic photosensitizer BDY with 2-Pyridone group has been synthesized for imaging-guided photothermal synergistic sustainable photodynamic therapy. Multifunctional water-soluble BDY nanoparticles (NPs), with high photothermal conversion efficiency of 35.7% and excellent singlet oxygen ( 1 O2 ) generation ability, are prepared by self-assembling. The reversible transformation between 2-pyridone moiety and its endoperoxide form endows BDY with continuous 1 O2 generation ability under illumination and non-illumination conditions. Simultaneously, BDY NPs exhibit excellent tumor targeting properties by enhanced permeability and retention (EPR) effect and photoacoustic imaging (PAI) ability. Furthermore, the photothermal assisted sustainable photodynamic therapy can significantly inhibit tumor growth (93.4% inhibition) with almost no side effects by intermittent laser illumination. The finding highlights that this photothermal synergistic sustainable phototherapy presents great potential for clinical applications.